Evaluasi Kepuasan Pengguna Aplikasi Inspekta di PT. PLN UP2D S2JB Menggunakan Metode Pieces - Aditya Revaldo; Imamulhakim Syahid Putra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to evaluate user satisfaction with the Inspekta Application at PT PLN UP2D S2JB using the PIECES Framework approach, which covers six key aspects: Performance, Information, Economy, Control, Efficiency, and Service. Data was collected through questionnaires distributed to 30 respondents who are active users of the application. The analysis results show that all PIECES indicators scored in the